Negotiating tradition and change in pastoral training in the Church of the Nazarene in Africa - Solomons, Lloyd (HTS teologiese studies, 2024)
This article highlights the tension of sustaining tradition versus the need for change within theological education. Within denominations, there is the challenge of maintaining tradition while at the same time wanting to embrace change. If this is not managed properly, the tradition can become out of date when there is a focus on controlling through enforcing tradition and through indoctrination in education. This article presents the Church of the Nazarene, as a case study, where their theological education is tested against an organic and indigenous framework highlighting the need for a contextual driven curriculum. There are various aspects within the tradition that are slow to adapt, where aspects of Western church polity and practices linger on thereby negatively impact the curriculum. However, if a contextual learning programme does not materialise students’ knowledge from the classroom will not match what they need to know once they reach the ministerial setting. This article examines pastoral training in the Church of Nazarene’s southern African region to emphasise the dichotomy between preserving tradition and the need to innovate in order to ensure its long-term viability.Contribution: This article reflects on the important balance of sustainability in a global church tradition, and it serves as a case study of issues commonly found in many denominations. It is about holding on to the core teachings that has stood the test of time but having the ability to be adaptative to the contextual needs of a region. Reasons are provided for the slow pace in change and ways to overcome this. This article contributes to the literature on the Church of Nazarene.